Recursos didácticos para la enseñanza aprendizaje de la unidad temática cónicas - Peña González, Santiago Efraín (2024)
Nowadays, it is necessary to use tools or materials that contribute to the development of students' competences. Consequently, this research entitled “Didactic resources for the teaching and learning of the conic thematic unit” aims to reduce the existing problem of not using didactic resources during the teaching and learning process in the area of mathematics, therefore, a guide of didactic resources for the teaching and learning of the Conic Sections is proposed for teachers and students of third year at Santa Mariana de Jesús Educational Unit during the 2023-2024 academic period, detailing activities, conceptual and procedural contents for the resolution of exercises and problems, a resource that will be very useful for teachers and students in the educational process. This research has a descriptive level of propositional, bibliographic, transversal type with nonexperimental design and quantitative approach. For data collection, the survey was applied as a technique and two questionnaires as instruments. The first one contains 24 questions sectioned into four dimensions, each one consisting of six items focused on identifying traditional and technological resources, attitude towards learning and teaching using a Likert scale with four options. On the other hand, the second one is an objective test made up of 15 questions each with four answer options focused on measuring the level of conceptual and procedural knowledge. These instruments were evaluated through the review of three professional teachers in the area of mathematics, who satisfactorily approved the application to a sample of 35 students selected in a non-probabilistic intentional way from the A and B sections of third year of high school who received the subject of analytical geometry; As a result of applying the diagnosis, we determined that the teacher does not use updated didactic resources and does not implement technology during the teaching-learning process of conic sections. In conclusion, a low level of conceptual and procedural knowledge is identified through the application of the objective test, evidencing that the implementation of didactic resources is fundamental, besides giving relevance to the present study in the elaboration of a guide of didactic resources focused on improving the learning experience and increasing the level of knowledge of the students, improving results in future research on conic sections.